2013
DOI: 10.1021/ml400271y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Quinazolone Derivatives as a New Class of c-KIT G-Quadruplex Binding Ligands

Abstract: The c-KIT G-quadruplex structures are a novel class of attractive targets for the treatment of gastrointestinal stromal tumor (GIST). Herein, a series of new quinazolone derivatives with the expansion of unfused aromatic ring system were designed and synthesized. Subsequent biophysical studies demonstrated that the derivatives with adaptive scaffold could effectively bind to and stabilize c-KIT G-quadruplexes with good selectivity against duplex DNA. More importantly, these ligands further inhibited the transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Quinazolone derivatives 76 – 83 have also been synthesized as G4 ligands (Figure ) . The FRET melting data demonstrate that all of the derivatives effectively stabilize the telomeric G4, exhibiting preference over dsDNA, as confirmed by competitive experiments.…”
Section: The Search For the Best Aromatic Modulesmentioning
confidence: 78%
See 2 more Smart Citations
“…Quinazolone derivatives 76 – 83 have also been synthesized as G4 ligands (Figure ) . The FRET melting data demonstrate that all of the derivatives effectively stabilize the telomeric G4, exhibiting preference over dsDNA, as confirmed by competitive experiments.…”
Section: The Search For the Best Aromatic Modulesmentioning
confidence: 78%
“…Quinazolone derivatives 82 and 83 containing an expanded aromatic system by the introduction of a benzene ring and a vinylphenyl group in the quinazolone moiety and two ionizable amino side chains have also been designed and studied . The FRET results show that compounds 82 a – c with shorter side chains have relatively modest G4 stabilizing ability, whereas compounds 82 d – f with longer chains induce increased T m values of the G4.…”
Section: The Search For the Best Aromatic Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating thiazole orange (29) [99] or a coumarinehemicyanine fluorophore (30) [100] to the isaindigotone framework lead to a big leap from colorimetric probe to colorimetric and fluorescent dual probe for detecting Gquadruplexes. In another series of quinazolinone derivatives (31) recently reported to stabilize c-KIT G-quadruplex, the best compound 31e reduced the transcription of c-KIT by 52.5% and exhibited significant cytotoxicity in a gastrointestinal stromal tumor cell line [101]. SAR analysis showed that the expanded aromatic system, via the introduction of a benzene ring, a benzylidene group and two cationic amino side chains into the quinazolone moiety, not only maximizes the stacking interaction of the derivatives with G-quartet but also incorporates features of flexibility that prevent it from intercalating into the duplex DNA.…”
Section: Quinazoline and Quinazolinone Derivativesmentioning
confidence: 99%
“…As a result of their diverse pharmacological activities such as anticancer [12,13], antimicrobial [14e16], antimalarial [17,18], anti-inflammatory [19e22], antihypertensive [23,24], anticonvulsant [25,26] and cholinesterase inhibition activities [27], these derivatives have received considerable attention. However, a lack of studies is clearly noticed that are to utilize the property that quinazolinone derivatives could arrest mutant p53 while maintaining steady-state protein levels.…”
Section: Introductionmentioning
confidence: 99%